Baroneurosis - Sanjay Kalra; Dina Shrestha; Rocco Barazzoni; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
Baroneurosis is a term used to describe distressful emotions and reactions related to weight, weight management, and weight monitoring, caused by irrational attitudes, behaviours, or choices, which lead to psychological and or physical symptoms, without impacting contact with reality, and without meeting the diagnostic criteria for any established psychiatric disease. Baroneurosis also known as weight neurosis, may concern the diagnosis, degree, and monitoring of weight-related disorders, or diet, exercise, lifestyle, and management. Various labels, including body dysmorphic traits, barometric nervosa, orthorexia nervosa, exertitium nervosa, and cyberchondria, are included under this umbrella. The concept of baroneurosis helps address the various psychosocial concerns, complaints, and challenges faced by various individuals as part of obesity management. It encourages physicians to view the person seeking weight management as a holistic person, with unique strengths and limitations, as well as opportunities for optimizing health. Keywords: Obesity, overweight, person-centred care, psychosocial aspects, psychiatry, psychology